Penggunaan Film Bahasa Inggris Untuk Meningkatkan Keterampilan Mendengarkan Siswa - Ratu Nafla Anissa Roshalina .HK (Journal Of Language Education and Development (JLed), 2023)
In recent years, learning media has developed very well in various types one of which is media in improving students' listening skills. Examples of possible media used is an English movie. By using this English movie there are many benefits obtained by students, namely, students can learn good English pronunciation directly from movies that is broadcast, students can add new vocabulary, students can learn good grammar and correct and also students can practice their listening skills. Apart from that, this movie can be used as a medium that can make students more active in taking classes, not boring and interesting so learning can go well. The aim of this research is to find out how much effective use of movie in improving students' listening skills in the field of language studies students' English, and also to find out students' perspectives on the use of movie as a medium learning. In the research conducted, the researcher used the literature study method with collect some data from various related journals for review in collecting data. The conclusion of this research is that the use of English movie improves abilities Listening to students is very effective. According to the student's perspective, the use of this film is very helpful them in learning.